Resiliência Psicológica: Revisão da Literatura e Análise da Produção Científica - Marilza Terezinha Soares de Souza; Ceneide Maria de Oliveira Cerveny (Interamerican Journal of Psychology, 2006)
This paper brings a literature review on psychological resilience, with a large survey about the researchs published since the concept was introduced in Health Sciences field. The survey includes national and international publications indexed in Medline, Lilacs, APA, SciELO Data Bases and, thesis and dissertations from Data Bases of CAPES and Universia. It is presented an analysis about the evolution of resilience issues and proposals for following researches.